Nilai Ekonomi Jasa Wisata Pulau Tangkil Provinsi Lampung Dengan Pendekatan Metode Biaya Perjalanan - Ahmad Effendi; Samsul Bakri; Rusita Rusita (Jurnal Sylva Lestari, 2015)
Tangkil island is one of the attractions in the province of Lampung is a relatively new development and the economic value is not known for many visitors. It is therefore necessary to research with the aim of determining the economic value of tourism services Tangkil Island and determine the effect of the characteristics of the visitors to the economic value of tourism services. Benefits of the research results can be used as a material consideration in determining management policies and the development of this attraction to the next. Research was conducted in December 2014-March 2015 with direct interview using questionnaires to 105 respondents. Determination of the results of the optimization parameters visitors travel costs were then tested by multiple linear regression method, using the software Minitab 16. The results reveal the total cost of the trip visitors Rp37,927,000/visit, the average cost of the trip visitors Rp 361,200/person/visit. The economic value of travel services is Rp10,888,284,096/year. The variable level of education at the level graduated from high school, the type of work to employers, additional employment, income, dependents in the family, the origin of visitors, visiting times when the Chinese New Year, Christmas and New Year, as well as the way of a visit has a Pvalue<0.1 so that the independent variables these have a significant influence on the economic value of tourism services Tangkil Island. The amount of standard deviation (S) is 77.20, while simultaneously influence the independent variable (R-Sq) is 78.6% and R-Sq (adj) is 70.2%. Keywords: Tangkil Island, cost of travel, economic value of tourism services